2018
DOI: 10.1111/myc.12762
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, stability study and preclinical evaluation of a vaginal cream containing curcumin in a rat model of vulvovaginal candidiasis

Abstract: Owing to the growing resistance among isolates of Candida species to usual antifungal agents and the well-known therapeutic potential of curcumin, the purpose of this study was to develop and validate a vaginal formulation containing this substance and to evaluating its effectiveness in the treatment of experimental vulvovaginal candidiasis. Curcumin was incorporated in a vaginal cream in three concentrations (0.01%, 0.1% and 1.0%). The different concentrations of the cream and its controls were intravaginally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Usual symptoms disappear within 2–3 days. [20] In the present study, azole compounds (clotrimazole) yielded the same results in regards to negative culture; curcumin, also, caused a 59.6% rate of negative cultivation. Although the effect of curcumin did not turn out to be as optimum as clotrimazole, further investigations can be conducted on this substance as an herbal remedy for treatment of vaginal symptomatic candidiasis.…”
Section: Discussionsupporting
confidence: 76%
“…Usual symptoms disappear within 2–3 days. [20] In the present study, azole compounds (clotrimazole) yielded the same results in regards to negative culture; curcumin, also, caused a 59.6% rate of negative cultivation. Although the effect of curcumin did not turn out to be as optimum as clotrimazole, further investigations can be conducted on this substance as an herbal remedy for treatment of vaginal symptomatic candidiasis.…”
Section: Discussionsupporting
confidence: 76%
“…Another non-invasive treatment option is the local application of curcumin containing formulations. A recent study used a cream containing 1.0% curcumin to treat vulvovaginal candidiasis in a rat model (Fernandes et al, 2018). The authors observed a reduction of fungal burden and inflammatory infiltration due to the cream.…”
Section: Antifungal Activities Of Curcuminmentioning
confidence: 99%
“…Topical administration of curcumin may be a fundamental solution to curcumin biomedical application because it remains local . Some topically curcumin formulations were applied for therapy of vaginal infection . Recently, smart polymer gels are focused on .…”
Section: Introductionmentioning
confidence: 99%